HEARING PUBLIK NASKAH AKADEMIK DAN DRAF RANPERDA TENTANG PEMBUDAYAAN GEMAR MEMBACA DI KABUPATEN SUMBAWA - Iwan Haryanto; Ade Safitri; I Gusti Made Sulindra; Abdul Rahim (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Public hearings are part of the sociological basis, where the provisions or regulations that are planned to be made must be in accordance with the general belief or legal awareness of the community. This means that academic texts and draft regional regulations regarding the Cultivation of Love of Reading must be in accordance with the will and legal awareness of the community. In an effort to obtain public views on the draft regional regulation, a public hearing was held involving all elements of society, ranging from community leaders, stakeholders, and students to other important elements. The stages of activity start from preparation, and implementation, namely the submission of the contents of the draft academic text and draft regional regulations, and finally discussion and evaluation